2001
DOI: 10.1094/pdis.2001.85.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Imidacloprid on Incidence of Tomato yellow leaf curl virus

Abstract: Confidor, an imidacloprid insecticide, was used in two applications at four rates (47.6, 71.4, 95.2, and 119 g a.i./ha) for indirectly controlling Tomato yellow leaf curl virus (TYLCV) in field plantings of tomato. This spray regimen was compared with standard applications of cypermethrins at 10- to 15-day intervals throughout the growing season. In three field trials, a combination of integrated pest management (IPM) practices and two applications of Confidor at the two highest rates immediately after plantin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
5
13
0
1
Order By: Relevance
“…Considering the cost of cultivation of different treatments, it is clearly indicated that T3 recorded the highest net return with highest B: C ratio though lowest disease incidence and white fly population/plant was recorded in T5. Our results well supported by observations of previous workers (Mullins et al, 1993, Ahmed et al, 2001and Cahill et al, 1996 and they recommended neonicotinoid group of insecticides (thiomethoxam, imidacloprid and dinotefuron) to reduce whitefly populations in order to save tomato plants against leaf curl virus diseases.…”
Section: Economics Analysis Of Different Treatmentssupporting
confidence: 93%
“…Considering the cost of cultivation of different treatments, it is clearly indicated that T3 recorded the highest net return with highest B: C ratio though lowest disease incidence and white fly population/plant was recorded in T5. Our results well supported by observations of previous workers (Mullins et al, 1993, Ahmed et al, 2001and Cahill et al, 1996 and they recommended neonicotinoid group of insecticides (thiomethoxam, imidacloprid and dinotefuron) to reduce whitefly populations in order to save tomato plants against leaf curl virus diseases.…”
Section: Economics Analysis Of Different Treatmentssupporting
confidence: 93%
“…Admire was found to be effective in reducing TYLCV incidence and resulted yield increase. The results are in agreement with the findings of Savary (2000) and Ahmed et al (2001). Imidacloprid (a systemic chloronicotinyl insecticide, Admire) gained major importance for controlling Bemisia tabaci in both field and protected crops, in view of extensive resistance to Organophosphorous, Pyrethroid and Cyclodiene insecticides (Cahil et al, 1995).…”
Section: B Discussionsupporting
confidence: 90%
“…Efficacy of imidacloprid to check tomato leaf curl virus under field conditions was also reported by Ahmed et al, (2001), who found that the repeated sprays of imidacloprid reduced disease incidence and the treated plots consistently had higher yields than control plots. Curling and cupping, with some reduction in leaf size of plant.…”
Section: Evaluation Of Insecticides Against Tomato Leaf Curl Virus (Tsupporting
confidence: 55%